Manatees - Marsh, Laura F. (Washington, D.C. : National Geographic, 2014)
Explores the world of manatees, including their habitats, physical characteristics, diet, behavior, and threats to their environment.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Description based on print version record.
Keywords: Manatees -- Juvenile literature; Manatees; Manatees; Electronic books- OSLIS; Juvenile works; Electronic books